Pemberdayaan Remaja Masjid Melalui Edukasi Olahraga Dan Perilaku Hidup Sehat Berbasis Nilai-Nilai Islam Di Kab. Pidie - Lestari, Indah; Faishol, Muhammad; Hamdani, Hamdani; Rahmi, Lisa (Institut Agama Islam Negeri (IAIN) Kudus, 2026)
The rapid transformation of adolescents' lifestyles in the digital era has increased sedentary behavior and reduced physical activity, while mosques have not been optimally utilized as community-based health promotion centers. This study aims to analyze the effectiveness of a mosque-based youth empowerment model through sports education and healthy lifestyle promotion integrated with the principles of Maqashid Sharia, particularly Hifz al-Nafs (the preservation of life), to strengthen the socio-religious role of mosques. The study employed a mixed-methods intervention evaluation design, combining a one-group pretest–posttest approach with qualitative data obtained through observation, semi-structured interviews, and participatory reflection involving 40 mosque youth members in Pidie Regency, Aceh, Indonesia. The findings indicate a significant improvement in participants' knowledge of physical activity and healthy lifestyle practices, accompanied by increased awareness that maintaining health constitutes an integral part of Islamic teachings. The intervention also facilitated the establishment of youth health cadres and mosque-based sports groups, thereby enhancing the institutional sustainability of community health promotion initiatives. These findings demonstrate that integrating community empowerment strategies with the Maqashid Sharia framework effectively revitalizes the mosque's role as a community health promotion center. This study contributes to the field of Islamic Community Development by proposing a Maqashid Sharia-Based Mosque Youth Health Empowerment Model, which integrates community empowerment, da'wah bil hal, and faith-based health promotion into a comprehensive framework for strengthening adolescent health and community well-being.